RETROPHARYNGEAL ABCESS IN ADULT - Tran, Hanh Uyen (Tạp chí Tai Mũi Họng Việt Nam, 2024)
Retropharyngeal abscess in adults can be life-threatening. The otorhinolaryngologist is on the front line in making the diagnosis and treatment of this disease. The aim of this study to review the clinical features, the diagnostic and the manegement of retropharyngeal abscess in adult. Patients and methods: Retrospective study of retropharyngeal abscess hospitalized in the ENT department from 2018-2023. Result: 5 patients in the study, average age 48, gender: 4 men and 1 woman. Paraclinical results include pre-operative CT scan, surgical treatment of pus drainage through the throat, combined with intravenous antibiotics. Postoperative pus culture results are group A Streptococcus susceptible to Amoxilline, 1 case of MRSA Staphylococcus. After a period of treatment at the hospital, all patients were stable and discharged. Conclusion: Retropharyngeal abscess is a critical infection in the deep neck space located in front of the spine and behind the esophagus. Patients need to be diagnosed quickly and accurately to have an intervention plan. CT scan imaging is the main important diagnostic method for accurate and timely diagnosis and intervention planning, especially differential diagnosis with abscesses caused by cellulitis. Treatment includes intravenous broad-spectrum antibiotics and surgical drainage of the abscess if necessary. The results are usually good.